(untitled) - Wallace, Michael J. (Cambridge, UK, 1998)
This practical guide can be used by teachers who wish to develop their professional expertise by investigating their own teaching in a systematic and organised way. It is also invaluable for teachers or trainee teachers who have to produce a professional project or dissertation as part of a training programme. This book will help teachers to design and implement a research project which is derived from their normal practice, with results which should be of direct relevance to them.The book is user-friendly and includes:- exemplar articles and extracts which show how the research techniques can be implemented- 'Personal review' sections which help readers to think about the ideas being discussed and relate them to their own situation- commentaries which follow up issues raised in the 'Personal review' sections- chapter summaries- a glossary of all technical terms
Keywords: English language; Study and teaching,Foreign speakers - research